Layanan Bimbingan Kelompok Untuk Meningkatkan Kepercayaan Diri Peserta Didik di Kelas XI SMA Negeri 1 Tondano - Parengkungan, Josua Vandy Ray; Sundah, Ariantje J. A (Peneliti.net, 2023)
This research aims to increase self-confidence through group tutoring services for some students in class XI SMA Negeri 1 Tondano. This research uses a type of counseling guidance action research, or (Action Research). The research subjects were 15 students from class XI who carried out two cycles with a design of action planning, observation and reflection. The data collection technique was carried out by three observers, namely the researcher, assisted by a guidance and counseling teacher at school and one subject teacher. The data analysis technique uses qualitative descriptive analysis. Research results or findings: In cycle I there were 12 students who achieved good criteria with increased self-confidence. Meanwhile, in cycle II, the results of observations showed that there was a significant increase, three students so that the 15 research subjects had experienced an increase in self-confidence. The conclusion of this research is that group guidance services can increase self-confidence in 15 class XI research subjects at SMA Negeri 1 Tondano.